2011
DOI: 10.1186/1556-276x-6-283
|View full text |Cite
|
Sign up to set email alerts
|

T cells enhance gold nanoparticle delivery to tumors in vivo

Abstract: Gold nanoparticle-mediated photothermal therapy (PTT) has shown great potential for the treatment of cancer in mouse studies and is now being evaluated in clinical trials. For this therapy, gold nanoparticles (AuNPs) are injected intravenously and are allowed to accumulate within the tumor via the enhanced permeability and retention (EPR) effect. The tumor is then irradiated with a near infrared laser, whose energy is absorbed by the AuNPs and translated into heat. While reliance on the EPR effect for tumor ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 47 publications
2
80
0
Order By: Relevance
“…For the treatment of experimentally induced tumors mainly lymphokine activated killer (LAK) cells, macrophages, mesenchymal stem cells, and erythrocytes were utilized as drug carriers (Batrakova et al, 2011). Delivered therapeutics include ricin (Cerundolo et al, 1987;Zanovello et al, 1992), doxorubicin and derivatives (Mandruzzato et al, 1994;Zocchi et al, 1989), liposomal 5-fluorouracil (Ikehara et al, 2006), nanoparticulate gold (Kennedy et al, 2011) as well as magnetic nanoparticles (Basel et al, 2012). In addition, genetically modified cells expressing immunotoxins, apoptosis-inducing proteins, and immunomodulating cytokines were tested in cell culture and animal experiments (Pereboeva and Curiel, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…For the treatment of experimentally induced tumors mainly lymphokine activated killer (LAK) cells, macrophages, mesenchymal stem cells, and erythrocytes were utilized as drug carriers (Batrakova et al, 2011). Delivered therapeutics include ricin (Cerundolo et al, 1987;Zanovello et al, 1992), doxorubicin and derivatives (Mandruzzato et al, 1994;Zocchi et al, 1989), liposomal 5-fluorouracil (Ikehara et al, 2006), nanoparticulate gold (Kennedy et al, 2011) as well as magnetic nanoparticles (Basel et al, 2012). In addition, genetically modified cells expressing immunotoxins, apoptosis-inducing proteins, and immunomodulating cytokines were tested in cell culture and animal experiments (Pereboeva and Curiel, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Previously, it has been shown that loading gold NPs into prostate, skin melanoma, and liver tumors, which are later exposed to irradiation, results in greater dose absorption within the tumor than the surrounding tissues 15, 16, 17, 18…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of nanoparticles can be done in a systemic way (through intravenous injection). 9,10 Many studies have been done in this field.…”
Section: Studies On Gold Nanoparticles (Au) Use In Combination With Lmentioning
confidence: 99%
“…On the other side near infrared (NIR) radiation is an interesting energy source as human blood and body tissues have the minimum absorption in this wavelength, thus deeper tissues can be reached. 9 The unique features of lasers such as photo-thermal properties and the extremely small size of nanoparticles (which creates new physical effects that are mainly a result of domination of the quantum properties in contrast to classical properties), provide an interesting combined therapeutic effect. Thermal therapy procures a fast recovery, shorter hospital stay, less complications and is easy to perform.…”
mentioning
confidence: 99%